Comparison of vaccination coverage of four childhood vaccines in New Zealand and New York State. (13th November 2018) - Baumann, Katherine E; Paynter, Janine; Petousis‐Harris, Helen; Prymula, Roman; Yang, Y Tony; Shaw, Jana
Abstract : Aim: To ensure that children are vaccinated, different national governments use diverse strategies. We compared childhood vaccination coverage rates between New York State (NYS) and New Zealand (NZ) as the vaccination strategies are different. Methods: We used vaccination records from the NYS Immunisation Information System and the National Immunisation Register of NZ to measure (i) vaccination coverage by school entry and by age six; (ii) coverage of different socio‐demographic groups; and (iii) trend in vaccination coverage between 2011 and 2015. Results: We analysed the records of 583 767 NYS children and 269 800 NZ children 7 years of age. NZ children were 3.3–21.5% more likely than NYS children to receive each of the vaccines. Compared to NYS, NZ children were 39.6% more likely to be up‐to‐date by the start of school and 28.1% more likely to be up‐to‐date by age 6 years. Both NYS and NZ had statistically significant increases in the proportion of children who were up to date on each vaccine and all vaccines by the start of school and by 6 years of age ( P < 0.001). Conclusions: We identified under‐vaccinated groups and examined the point in the vaccine series where children were most vulnerable to being under‐vaccinated. This information is useful in targeting future investigations and interventions aimed at mitigating disparities in vaccine coverage. This comparison of regions with different vaccination programmes and policies is important when considering whether the particular vaccination coverage strategies of one region could be adapted and applied for the benefit of another.